Respostas

2013-12-13T12:29:54-02:00
(1.)  y = x2 + x - 30          

      0 = (x + 6)(x - 5)           
    x + 6 = 0    x - 5 = 0    
       -6 -6      +  5  +5   
   
        x = -6  ,    x = 5      

(ii.) y = 02 + 0 - 30 

      y = -30      

(iii.)   y' = 2x + 1     

          2x + 1 = 0   

              -1  -1   
       
          2x  =  -1      
         ____   ____
            2     2       

            x = -1/2
??
Comentário foi eliminado
Comentário foi eliminado
tá diireeeito , :))
tá correeeto , ^^